Does SARS-CoV-2 in Pregnancy Affect Newborn Outcomes? - Marjana Jerković Raguž; Jerko Brzica; Svjetlana Grgić; Vedran Bjelanović; Antonija Mustapić; Darinka Šumanović Glamuzina; Mirela Mabić (IMR Press, 2022)
Background: The aim of this study was to show the frequency and epidemiological characteristics of pregnant women who tested positive for SARS-CoV-2 during childbirth as well as the course, mode and outcome of their newborn treatment and diet after discharge. The aim is also to show individual symptoms developed by newborn from pregnant women who test positive for SARS-CoV-2. Method: The study included all the infants born to the pregnant women who tested positive for SARS-CoV-2 on a PCR test 24 hours prior to delivery or, had already been confirmed positive for the infection and had developed symptoms of the virus or had started treatment for SARS-CoV-2 several days prior to delivery. Results: 43/3237 (1.32%) of the pregnant women tested positive for the SARS-CoV-2 virus or had been infected prior to admission and were positive during delivery. A total of 45 newborn infants were transferred to a special room for the care of newborn infants born to SARS-CoV-2-positive mothers at the Department of Neonatology. Specifically, 30/45 (66.7%) of the newborn infants developed symptoms within the first hours of birth which withdrew spontaneously within 24-48 hours after birth. The symptoms referred to are not specific forSARS-CoV-2 infection and are not particularly indicative of infection. Conclusions: The conclusion of this short 21-month study is that prenatal and postnatal duration and outcome in infants is not aggravated by pregnant women who tested positive for SARS-CoV-2. Despite the individual symptoms described above and the pathological states the children developed during hospitalization, all the newborn infants were discharged from hospital in full health, and they were all breastfeeding following discharge in conditions which respected all the epidemiological preventive measures.